Bio-Guided Isolation of Two New Hypoglycemic Triterpenoid Saponins from Polygonum capitatum - Huang D; Du Z; Chen Y; Dong Z; Wang X; Li M; Zhang F; Chen W; Sun L (Dove Medical Press, 2021)
Doudou Huang,1,2,* Zenan Du,1,2,* Yanhong Chen,3,* Zhiying Dong,1 Xiujuan Wang,1 Mengshuang Li,1 Feng Zhang,3,* Wansheng Chen,2,3 Lianna Sun1 1Department of TCM Processing, Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China; 2Institute of Chinese Materia Medica, Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China; 3Department of Pharmacy, Changzheng Hospital, Second Military Medical University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Lianna Sun; Wansheng Chen Tel/Fax +86-21-51322211Email sssnmr@163.com; chenwansheng@smmu.edu.cnPurpose: Diabetes is a common disease caused by a combination of genetic and environmental factors, which was the top three diseases threatening human health. Therefore, it is necessary to seek more efficient hypoglycemic drugs. The main objective of this study was to investigate the potential hypoglycemic effects of compounds from Polygonum capitatum.Materials and Methods: Our experiments were divided into three steps: (1) α-amylase test and oral starch tolerance test (OSTT) for screening the biological extract part of P. capitatum; (2) chemical isolation and identification using various separation techniques, and spectrum methods; and (3) evaluation of α-amylase inhibitory activity of isolates and in silico analysis for mechanism investigation.Results: The n-butanol fractioned part of P. capitatum was confirmed to be the biological part according to α-amylase test. Then, two new triterpenoid saponins were isolated from the n-butanol part, which were also the first isolated triterpenoid saponins from P. capitatum. The activities of compounds 1 and 2 against α-amylase were 51.9± 2.8% and 38.1± 2.2%, respectively, which was consistent with the molecular docking analysis. In which, 1 and 2 showed the binding affinity energy for α-amylase was − 9.4 kcal/mol and − 7.8 kcal/mol, respectively.Conclusion: Two new triterpenoid saponins were firstly isolated from P. capitatum, and displays potency as a hypoglycemic agent through blocking α-amylase.Keywords: α-amylase, Polygonum capitatum, triterpene saponins, hypoglycemic